Approach to Obtain Electrospun Hydrophilic Fibers and Prevent Fiber Necking. Issue 12 (17th October 2019) - Fischer, Thorsten; Möller, Martin; Singh, Smriti
Abstract: Solution electrospinning of a blend containing a hydrophobic polymer with a hydrophilic functional polymer as an additive is a simple and straight‐forward route to obtain functional and hydrophilic fibers accompanied by the mechanical properties of the hydrophobic polymer. However, this process of thermodynamically unfavored surface segregation of the hydrophilic additive is not well understood. To understand the process the dependencies of the surface hydrophilization on type of hydrophilic polymers, the solvent, and the process, using poly(caprolactone) (PCL) as the matrix polymer is explored. The results show that hydrophilic fibers can be obtained using different additive hydrophilic polymers. The combination of polymer blends which show this effect can be predicted using the Flory–Huggins interaction parameter. In addition mechanical and micromechanical properties of PCL fibers blended with NCO‐terminated star‐shaped poly(ethylene glycol) (sPEG‐NCO) as additive are investigated. In this context blending with sPEG‐NCO turns out to be a powerful tool to prevent fiber necking rendering this method an interesting candidate for tissue engineering application, where it is mandatory to retain the surface properties under mechanical stress. Abstract : Electrospinning of a polymer blend is a facile and versatile method to obtain hydrophilic fibers exploiting thermodynamical unfavored surface segregation. Poly(caprolactone) is used as a matrix polymer to develop a rationale and to understand this process. Additionally, the macro‐ and micro‐mechanical properties of the meshes using isocyanate terminated star shaped poly(ethyleneglycol) are investigated revealing that fiber necking can be prevented.